Penggunaan Video Sebagai Media Pembelajaran Pada Matakuliah Grafika Komputer - Harmastuti Harmastuti; Dwi Setyowati; Agus Marsadualan (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
Due to the Covid-19 pandemic in 2019 to 2021, learning activities are carried out online. This is done to reduce physical contact and try to follow the health protocol that has been recommended by the government. For this reason, it is necessary to have learning methods that must be taken, to address this, one of which is the delivery of learning that can be done based on video. This study discusses Video and Powerpoint (PPT) based Computer Graphics learning media, this aims to increase understanding of learning material delivered online (online). In its implementation, video material and PPT for Computer Graphics course semester 6 were made using software (PPT) and Wondershare Filmora Video Editor. As a test sample, the Introduction to computer graphics chapter was taken with Descriptive Analysis using excel, Analysis (Hypothesis Testing) Independent Samples T-Test Method with a significance level of 5% using SPSS, from 9 (nine) respondents, on the material and learning media. Evaluation of learning outcomes used an assessment of the range of scores 1 to 6 (six) for the learning media and 11(eleven) questions related to the understanding of the material. The results showed that the teaching method using video media resulted in an average score of correct answers greater than the average score of correct answers using PPT teaching media. The percentage for video learning media strongly agree (sss) 40.28%, while the PPT learning media assessment strongly agrees (sss) 37.04%.